Impact of wheelchair seat height on neck and shoulder range of motion during functional task performance. Issue 3 (2nd July 2016) - Sabari, Joyce; Shea, Mary; Chen, Linda; Laurenceau, Alyssa; Leung, Evan
ABSTRACT: Wheelchair users are at high risk for developing repetitive stress injuries (RSI) of the cervical spine and glenohumeral joints due to increased demands on active range of motion (AROM) when performing functional tasks from a seated position. The addition of a seat elevation device may alleviate the risk factors that lead to the development of RSI. However, there are no studies which establish that wheelchair seat height impacts upon arthrokinematic requirements at vulnerable joints. Additionally, Medicare and most insurance carriers do not cover the cost of power seat elevators because this feature has not been shown to be a "medical necessity." This study examined differences in AROM at the cervical spine and glenohumeral joint during performance of two functional tasks while seated in a wheelchair with the seat elevation feature at minimum and maximum height. Results revealed statistically significant differences in AROM requirements for cervical extension and shoulder abduction between the two wheelchair seat heights. These findings provide preliminary support for the value of the power seat elevation function in minimizing the risk of RSI at the shoulder complex and cervical spine in wheelchair users.